Lebanon Economic Monitoring Note, September 2012 - World Bank (Washington, DC, 2017)
The stalemate between domestic political forces continues to impede reforms while the ongoing Syrian conflict is imposing a security, political, and economic toll on Lebanon. The stalemate in the executive and legislative branches of government remains an impediment to reforms. Important bills, regulations and appointments are still pending in cabinet and Parliament. This deadlock could well last until the June 2013 Parliamentary elections. The Syrian crisis is fueling political divide among sectarian lines in Lebanon, leading to sporadic violence incidents across the country. These incidents have materially impacted the economy, with sectors such as tourism strongly affected. Politically, the turmoil has sparked social unrest and overshadowed the reform drive. To tackle the situation, the government devised a minimum political understanding to restore order in the country. Political backing for a large security operation has also been given; results have yet to fully materialize. The fiscal deficit and public debt positions remain major challenges for the Lebanese economy. The fiscal deficit deteriorated somewhat during the first half of the year. Notwithstanding this slight widening of the fiscal balance, public debt continues its recent downward trend. Rising international commodity prices and the Syrian crisis are adding further pressure on both trade and current account deficits.